Measurement of dispersion of low-frequency ion oscillations in hybrid plasma waveguides - Antipov, V.S.; Antonov, A.N.; Balakirev, V.A.; Kovpik, O.F.; Kornilov, E.A.; Matyash, K.V.; Svichensky, V.G. (Вопросы атомной науки и техники, 2005)
A new technique of determining dispersion characteristics of the ion oscillations, excited in the hybrid plasma waveguide is elaborated (this device is a slow-wave structure, the passage channel of which is filled with plasma). This method is based on measuring changes in the shape of a single probing pulse propagating in the system. The method is tested in the process of determining the dispersion of low-frequency ion waves under the condition of the excitation of high-frequency powerful electron oscillations by an electron beam in the waveguide. The experimental data are compared with the analytical calculations.